2015
DOI: 10.1021/nl504929n
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Doping Concentration and Nonradiative Lifetime Profiles in Single Si-Doped InP Nanowires Using Photoluminescence Mapping

Abstract: We report an analysis method that combines microphotoluminescence mapping and lifetime mapping data of single semiconductor nanowires to extract the doping concentration, nonradiative lifetime, and internal quantum efficiency along the length of the nanowires. Using this method, the doping concentration of single Si-doped wurtzite InP nanowires are mapped out and confirmed by the electrical measurements of single nanowire devices. Our method has important implication for single nanowire detectors and LEDs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(78 citation statements)
references
References 54 publications
3
75
0
Order By: Relevance
“…It is well known that due to background impurity doping, the unintentionally doped InP grown by MOVPE is normally n‐type . We also found that the InP NWs grown by the SAE technique exhibit a relatively high background doping density of ~10 17 cm −3 , which has to be taken into consideration when designing p‐n junction for solar cell applications. In this work, three different InP NWSC structures grown on p‐doped InP substrate by SA‐MOPE, namely i(n − )‐n, p‐i(n − )‐n, and p‐p − ‐n, were designed and characterized using EBIC technique.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…It is well known that due to background impurity doping, the unintentionally doped InP grown by MOVPE is normally n‐type . We also found that the InP NWs grown by the SAE technique exhibit a relatively high background doping density of ~10 17 cm −3 , which has to be taken into consideration when designing p‐n junction for solar cell applications. In this work, three different InP NWSC structures grown on p‐doped InP substrate by SA‐MOPE, namely i(n − )‐n, p‐i(n − )‐n, and p‐p − ‐n, were designed and characterized using EBIC technique.…”
Section: Introductionmentioning
confidence: 72%
“…Sample III (p‐p − ‐n + ) was grown with a p‐doped section (1.5 minutes) on the p + substrate followed by a lightly p‐doped section (5 minutes) and a heavily n‐doped section (1.5 minutes). The doping concentrations of both n‐doped and undoped sections were calibrated based on our previous doping study . However, despite a high doping concentration aimed for the bottom p‐region for samples II and III, we find it difficult to determine the p‐type doping concentration using both the photoluminescence (PL) and electrical measurements which were previously used to determine the n‐type doping concentration with great success, implying that the p‐region of our NWs may be only lightly doped (<1 × 10 17 cm −3 ) despite that a high diethylzinc (DEZn) flow rate was used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…38,49 Another relevant study under a pulsed excitation condition was also conducted and would be of interest here as well. 50 Figure 3a lays out the experimental setup used to implement this method. It consists of the aforementioned μ-PL setup (blue background), in conjunction with time-correlated singlephoton counting (TCSPC) facility (pink background) for TRPL measurement (see ref 35 for details).…”
Section: Nano Lettersmentioning
confidence: 99%